2016
DOI: 10.3390/ijms17060920
|View full text |Cite
|
Sign up to set email alerts
|

Finding a Potential Dipeptidyl Peptidase-4 (DPP-4) Inhibitor for Type-2 Diabetes Treatment Based on Molecular Docking, Pharmacophore Generation, and Molecular Dynamics Simulation

Abstract: Dipeptidyl peptidase-4 (DPP-4) is the vital enzyme that is responsible for inactivating intestinal peptides glucagon like peptide-1 (GLP-1) and Gastric inhibitory polypeptide (GIP), which stimulates a decline in blood glucose levels. The aim of this study was to explore the inhibition activity of small molecule inhibitors to DPP-4 following a computational strategy based on docking studies and molecular dynamics simulations. The thorough docking protocol we applied allowed us to derive good correlation paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 36 publications
0
24
0
1
Order By: Relevance
“…To attend this problem, several in silico studies have been carried out to predict which compounds of Ephedra , such as (−)-ephedrine ( 1 ) and five ephedrine derivatives 2 – 6 have potential antidiabetic properties by inhibiting dipeptidyl peptidase IV (DPP-IV). These studies are based on the fact that these compounds are considered oral hypoglycemic agents because they reduce glucagon and blood glucose levels mediated by increasing incretins that are responsible for inhibiting the release of glucagon and for promoting an increase in insulin secretion [ 117 , 118 , 119 ]. Oh et al showed that E. sinica Stapf normalizes hyperglycemia and hyperinsulinemia in obese mice (C57BL/6J), that were fed a high-fat diet [ 120 ].…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…To attend this problem, several in silico studies have been carried out to predict which compounds of Ephedra , such as (−)-ephedrine ( 1 ) and five ephedrine derivatives 2 – 6 have potential antidiabetic properties by inhibiting dipeptidyl peptidase IV (DPP-IV). These studies are based on the fact that these compounds are considered oral hypoglycemic agents because they reduce glucagon and blood glucose levels mediated by increasing incretins that are responsible for inhibiting the release of glucagon and for promoting an increase in insulin secretion [ 117 , 118 , 119 ]. Oh et al showed that E. sinica Stapf normalizes hyperglycemia and hyperinsulinemia in obese mice (C57BL/6J), that were fed a high-fat diet [ 120 ].…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…CDOCKER is a semi-flexible molecular docking analysis method based on the CHARMm force field, which can produce high-precision docking results, and it provides information on the interaction binding energy and ligand-receptor docking mode [28]. According to the molecular docking results of CDOCKER (Table 3), CDOCKER interactions and binding energies for three of the seven compounds were better than vildagliptin [29]. Therefore, compounds 1-3 may be potential DPP-IV inhibitors based on the above virtual screening and docking processes.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, molecular docking is extensively used for virtual investigation of the interactions between ligands and receptors, which can help to reveal the binding modes and the residues involved in binding interactions. In order to identify potential DPP-IV inhibitors, binding models for interactions between the active sites of DPP-IV, and the inhibitors have been proposed in several investigations [ 18 ]. In the present study, a molecular docking strategy was used to screen the 57 identified peptides and identify DPP-IV inhibitory peptides.…”
Section: Resultsmentioning
confidence: 99%